Analisis Perbandingan Kinerja Keuangan dan Nilai Perusahaan Sebelum dan Di Saat Pandemi Covid-19 - Nurul Febriani, Annisa; Dharmawan Buchdadi, Agung; Suryawan Siregar, M. Edo (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to determine whether or not there were differences in financial performance and firm value before and during the Covid-19 pandemic in the mining sector and the consumer goods industry sector which were listed on the Indonesia Stock Exchange in 2018-2021. Financial performance is measured by Earning Per Share (EPS) and firm value is measured by Price Earning Ratio (PER). This research includes quantitative research with research populations in the mining sector and the consumer goods industry sector which are listed on the Indonesia Stock Exchange in 2018-2021. The sample is determined by purposive sampling technique. The data analysis method used the Wilcoxon Signed Test with a total sample of 40 companies in the mining sector and 44 companies in the consumer goods industry sector. The data is processed using SPSS software version 25. The results show that there is a difference in the financial performance of the mining sector and there are no differences in the firm value in the mining sector. In the consumer goods industry sector, there are no differences in financial performance and firm value.